PTH-057 Dendritic cell phenotype in crohn's disease may correlate with disease severity and explain the high prevalence of cutaneous manifestations. (22nd June 2015) - Hendy, PA; Bernardo, D; Al-Hassi, HO; Ding, NS; Reddi, D; Siaw, YH; Knight, S; Hart, AL
Abstract : Introduction: Dendritic cells (DC) are potent antigen presenting cells that bridge the innate and adaptive immune systems. Altered function and phenotype of human blood DC has been described in inflammatory bowel diseases including Crohn's disease (CD), with peripheral blood DC displaying more inflammatory and fewer tolerogenic characteristics in CD than in healthy controls (HC). However, the correlation between CD severity and the expression of DC phenotypic molecules is still unknown. Here we use flow cytometry to assess this correlation. Method: Blood was taken from patients with CD and HC and a Ficoll density gradient was used to separate and isolate the peripheral blood mononuclear cells. Multicolour flow cytometry was performed to assess DC which were identified as being both HLA-DR positive and negative for the usual DC lineage markers (CD3, 14, 16, 19, 32). DC were further divided as myeloid (mDC, CD11c+CD123-) and plasmacytoid (pDC, CD11c-CD123 + ). Expression of co-stimulatory and homing molecules on DC was assessed by flow cytometry. Disease severity was assessed by both the Harvey-Bradshaw index and by faecal calprotectin. Results: 6 patients with CD and 2 HC were recruited. Expression of the co-stimulatory molecules CD40 and CD80 on mDC correlated with disease severity as assessed by the Harvey-Bradshaw index (p = 0.078 and 0.048 respectively) and the same was found on pDC (p = 0.008 and 0.0311 respectively). There was a non-significant trend toward correlation for the co-stimulatory molecule CD86 (p = 0.065). Expression of the homing marker CLA (skin homing) was raised in CD (p = 0.043) and correlated with disease severity (as assessed by faecal calprotectin levels) in CD (p = 0.0078). Conclusion: A correlation between expression of DC co-stimulatory molecules and CD severity was found. This is a novel finding and suggests a potential role for these molecules as biomarkers. We also show that peripheral blood DC expression of the skin homing molecule CLA is higher in CD than in healthy controls and increases in more active disease. This may help explain both the high rates of cutaneous manifestations (including erythema nodosum) in CD, and the fact that these cutaneous presentations most often occur in the context of active disease. Disclosure of interest: None Declared.